Leveraging the public health emergency operation center for pandemic response: opportunities and challenges (2020)
Public Health Emergency Operation Center (PHEOC) was conceptualized and established for coordinating information and resources towards goal-oriented response in large scale public health emergency. Yet, the activities undertaken by PHEOCs and their intended goals have not been fully optimized in current scenario. This paper revisited the collective efforts invested in PHEOC conceptualization and development, identified the opportunities and challenges in compliance with standards and framework, demonstrated the accountability of PHEOC network, thereby promoted best practice guidance for global public health emergency preparedness and response. This review will help navigate emergency response complexities leveraging PHEOC partnerships and advance the ability to detect and respond to public health emergencies in low resource settings. The review shows that the information on how to adapt best practice guidance to local circumstances could incentivize the full implementation of prevention, early detection and response to outbreaks. Identifying and correcting deficiencies in effectiveness evaluation will provide the basis for continuous PHEOC improvement. With the gradually reopening economies and public services in some countries, there is an urgent need to emphasize and validate the collective efforts undertaken by PHEOCs for tackling the COVID-19 pandemic.